THE CHANGES OF ZINC, COPPER, AND IRON LEVELS IN LUNG TISSUE AFTER FORMALDEHYDE INHALATION DURING THE EARLY POSTNATAL PERIOD OF RATS - Songur, Ahmet; Kus, Ilter; Sahin, Semsettin; Sogut, Sadik; Ozen, Oguz Aslan; Yaman, Mehmet; Sarsilmaz, Mustafa (Modestum Ltd, 2005)
Aim: In this study, effects of inhaled formaldehyde ( FA) gas, during early postnatal period on the levels of zinc, copper and iron elements and activity of total superoxide dismutase (t-SOD) enzyme in lung tissue and also the reversibility of effects of formaldehyde were examined. Methods: For this purpose newly born albino Wistar rats were exposed to 0 ( control), 6 or 12 ppm FA gas for 30 days. After the treatment, rats were decapitated in 30th and 90th days. Activities of t-SOD and the levels of zinc, copper and iron were measured in lung samples. Results: A decrease in the t-SOD activity, copper and iron levels and increase in zinc levels were found in the treatment groups in comparison with control group at both 30th and 90th days measurements. Conclusion: It was thought that exposure to FA may alter the trace element levels of lung tissue including copper, zinc and iron, and induce further oxidative damage on lung tissue.
Keywords: Formaldehyde gas; lung; t-SOD; zinc; copper; iron